Eslicarbazepine-induced hyponatremia: A retrospective single-center real clinical practice study - Strýček, Ondřej; Všianský, Vít; Doležalová, Irena; Kočvarová, Jitka; Pail, Martin; Brázdil, Milan (Epilepsia open, 2024)
Hyponatremia is a typical side effect of antiseizure drugs from the dibenzazepine family. The study investigated the prevalence of hyponatremia in patients with epilepsy who were treated with eslicarbazepine. We aimed to determine the prevalence of hyponatremia, reveal the factors leading to the discontinuation of treatment, and identify possible risk factors for the development of hyponatremia including the dose dependency. The medical records of 164 patients with epilepsy taking eslicarbazepine in our center were analyzed. The overall prevalence of hyponatremia was 30.5%. The prevalence of mild hyponatremia, seen in 14%-20% of patients, was not dose dependent. The prevalence of moderate and severe hyponatremia was significantly dose dependent. The severity of hyponatremia was significantly dose dependent. Severe hyponatremia was found in 6.1% of patients. Hyponatremia was asymptomatic in the majority of cases, and in 48% did not require any management. Hyponatremia was the reason for discontinuation in 6.2% of patients. The major risk factor for developing hyponatremia was older age. The study shows that eslicarbazepine-induced hyponatremia is usually mild and asymptomatic. It usually does not require any management and seldom leads to treatment discontinuation. Hyponatremia is dose dependent. Another major risk for developing hyponatremia (besides dose) is older age.
Keywords: epilepsie; Retrospective Studies; Hyponatremia; retrospektivní studie; Anticonvulsants; dibenzazepiny; antikonvulziva; Dibenzazepines; Humans; lidé; Epilepsy; hyponatremie